Monitoring Antimicrobial Susceptibility in bacterial isolates causing Urinary Tract Infections in a Tertiary Hospital in Kathmandu - Singh, Vivek Kumar; Chaudhary, Mahesh Kumar; Banjara, Megha Raj; Tuladhar, Reshma (Nepal Journal of Science and Technology, 2020)
Urinary tract infection is the most common infection in females worldwide. One in three women experiences at least one episode of urinary tract infection during their lifetime. The objective of this study was to determine the etiology and antimicrobial profile of urinary tract infection. A cross-sectional study was conducted at a tertiary care hospital in Nepal. Thirteen hundred clean catch mid-stream urine samples were tested through standard microbiological techniques. The isolates from urine samples were identified from biochemical tests. Antibiotic susceptibility testing was performed through the Kirby-Bauer disc diffusion technique following CLSI guidelines. The prevalence of urinary tract infection was found at 24.23%. Escherichia Coli was a predominant etiological agent followed by Staphylococcus aureus. The majority of the infection was found between the age group 21-40, with females mostly infected. Most of the microorganisms were isolated from emtergency, obstetrics-gynecology, and nephrology wards. Most of the isolates were resistant to ampicillin, whereas the majority of the gram-positive isolates were resistant to penicillin.A large number of isolates were found to be sensitive to Gentamycin and nitrofurantoin. Routine antimicrobial susceptibility testing of the isolates causing urinary tract infection is recommended to reduce antimicrobial resistance and for the proper treatment of infection.